Computational Shape Design Optimization of Femoral Implants: Towards Efficient Forging Manufacturing - Garcia-Herrera, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Total hip replacement is one of the most successful orthopedic operations in modern times. Osteolysis of the femur bone results in implant loosening and failure due to improper loading. To reduce induced stress, enhance load transfer, and minimize stress, the use of Ti-6Al-4V alloy in bone implants was investigated. The objective of this study was to perform a three-dimensional finite element analysis (FEA) of the femoral stem to optimize its shape and analyze the developed deformations and stresses under operational loads. In addition, the challenges associated with the manufacturing optimization of the femoral stem using large strain-based finite element modeling were addressed. The numerical findings showed that the optimized femoral stem using Ti-6Al-4V alloy under the normal daily activities of a person presented a strains distribution that promote uniform load transfer from the proximal to the distal area, and provided a mass reduction of 26%. The stress distribution was found to range from 700 to 0.2 MPa in the critical neck area of the implant. The developed computational tool allows for improved customized designs that lower the risk of prosthesis loss due to stress shielding. © 2024 by the authors.